All Maximal Idempotent Submonoids of the Set of Generalized Hypersubstitutions of Type (n) - Weerapong Wongpinit (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
In this work, we are interested to investigate the structure of all maximal idempotent submonoids of HypG(n) which is the set of all generalized hypersubstitutions of type T = (n) by starting with n = 2. And then we generalize to arbitrary natural number type. Moreover, we study the relationship between some regular subsemigroups of HypG(2) and determine the set of some special regular elements of the monoid HypG(2).